(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article discusses the monetary levers of asset diversification, which are important in stabilizing the risks of commercial banks. In addition, the foreign experience of effective assessment of the level of risks is studied and recommendations are given for its implementation.